Proccedings of International Scientific Conference "RURAL DEVELOPMENT 2017" 2018
DOI: 10.15544/rd.2017.217
|View full text |Cite
|
Sign up to set email alerts
|

Organic Farming as a Part of the Sustainable Development of Agriculture

Abstract: The paper presents the relationships of organic farming with sustainable development of agriculture and rural areas. The promotion of environmentally friendly agriculture and environmental protection are implemented within agri-environmental programs. The aim of these programs is to achieve sustainable rural development and preserve biodiversity. The goal of studies was to assess the sustainability of ecological agriculture at the level of an agricultural holding. Organic farming is perceived as a system that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Brenann et al [22] demonstrated that measuring sustainability allowed for comparisons between farmers who use extension services and those who do not among eight EU countries. Basing their paper on the FADN network, Koloszko-Chomentowska and Zukovskis [23] explored the sustainability of organic farming versus conventional farming in Poland. Reidla and Nurmet [24] examined dairy farms' economic, social, and environmental dimensions of sustainability and compared them between the Baltic States using the FADN database.…”
Section: Review Of the Farm Sustainability Assessment Based On Fadn Datamentioning
confidence: 99%
“…Brenann et al [22] demonstrated that measuring sustainability allowed for comparisons between farmers who use extension services and those who do not among eight EU countries. Basing their paper on the FADN network, Koloszko-Chomentowska and Zukovskis [23] explored the sustainability of organic farming versus conventional farming in Poland. Reidla and Nurmet [24] examined dairy farms' economic, social, and environmental dimensions of sustainability and compared them between the Baltic States using the FADN database.…”
Section: Review Of the Farm Sustainability Assessment Based On Fadn Datamentioning
confidence: 99%